2019
DOI: 10.1055/s-0038-1677516
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein (MCP)-1 in Rotavirus-Associated White Matter Injury in Newborns

Abstract: Recent reports have suggested an association between rotavirus infection and a distinctive pattern of white matter injury (WMI) in neonates with seizures; however, the connection between the two is not fully understood. To evaluate the underlying mechanism, we profiled and compared eight cytokines (IL [interleukin]-1β, IL-6, IL-8, IL-10, IFN-γ [interferon-γ ], MCP-1 [monocyte chemoattractant protein-1], MIP-1β [macrophage inflammatory protein-1β], and TNF-α [tumor necrosis factor-α]) in the cerebrospinal fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…14,113) Newborns with rotavirus-associated leukoencephalopathy have significantly higher IL-6, IFN-γ, and monocyte chemoattractant protein-1 levels in the CSF than the control group. 114,115) Furthermore, CSF…”
Section: Cns Entry Of Circulating Mediators Produced By Rotavirus Inf...mentioning
confidence: 99%
See 1 more Smart Citation
“…14,113) Newborns with rotavirus-associated leukoencephalopathy have significantly higher IL-6, IFN-γ, and monocyte chemoattractant protein-1 levels in the CSF than the control group. 114,115) Furthermore, CSF…”
Section: Cns Entry Of Circulating Mediators Produced By Rotavirus Inf...mentioning
confidence: 99%
“…Clinical studies have shown that rotavirus gastroenteritis is associated with increased levels of proinflammatory cytokines, such as IL-1β, IL-6, IL-8, and interferon gamma (IFN-γ) [ 14 , 113 ]. Newborns with rotavirus-associated leukoencephalopathy have significantly higher IL-6, IFN-γ, and monocyte chemoattractant protein-1 levels in the CSF than the control group [ 114 , 115 ]. Furthermore, CSF IL-6 levels correlate positively with white matter lesion extent.…”
Section: Proposed Potential Mechanisms Of Rotavirus Infection-associa...mentioning
confidence: 99%